Fine needle aspiration cytology of mesenchymal hamartoma of liver mimicking hepatoblastoma: A case report. Issue 10 (15th July 2021) - Thakur, Shilpi; Yadav, Rajni; Agarwala, Sandeep; Jana, Manisha; Jain, Deepali; Mathur, Sandeep R.; Iyer, Venkateswaran K.
Abstract: Fine‐needle aspiration cytology (FNAC) is an effective tool for early and quick diagnosis of malignant and metastatic liver masses. However, diagnosing a benign liver tumor on cytology is a challenging task as they are rarely assessed on cytology and also due to the limitations of the procedure. Mesenchymal hamartoma is an uncommon benign pediatric liver tumor and difficult to diagnose on cytology. We describe here a case of a child who presented with a huge liver mass and clinical suspicion of hepatoblastoma. The child underwent blind FNA, and was diagnosed as mesenchymal hamartoma based on the cytological features. A biopsy was performed subsequently which confirmed the same and then he underwent surgical resection of the tumor. The patient had an uneventful recovery and is disease free on follow up.